CLASSIFICATION OF NAMES USED IN LITERARY WORKS (BASED ON THE NOVEL 'AMIR TEMUR' BY BO'RIVOY AHMEDOV) - Doniyeva Khurshida Uktamovna (Modern American Journals, 2025)
This article provides a systematic analysis of names used in literary texts, with particular attention to their structural and semantic characteristics. The novel "Amir Temur" by Bo'rivoy Ahmedov serves as the main object of study, with classification of personal names, place names, historical and mythological references found throughout the text. The article examines the functional load of names, their role in character creation, and their reflection of national and cultural consciousness through a linguocultural lens. This reveals how names fulfill aesthetic and semantic functions within the narrative, harmonizing historical truth with artistic interpretation.The findings of this research serve as a methodological foundation for the study of toponymic and anthroponymic units in literary analysis, highlighting their role in artistic expression and addressing challenges in literary translation.